BDNF improves the survival of mesenchymal stem cells cultured on pre-structured gelatin material containing strontium and calcium phosphates for bone regeneration - Itting, Paul T.; Kruppke, Benjamin; Hanke, Thomas; Vijayan, Vinu; Heiss, Christian; Lips, Katrin Susanne (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThe treatment of osteoporotic fractures is still challenging and may be improved using materials for bone regeneration, such as pre-structured gelatin with calcium and strontium phosphates (PPGC+S), combined with brain-derived neurotrophic factor (BDNF). Recently, it was shown that PPGC+S stimulates bone formation, and BDNF improves cell survival. This study aimed to analyze the combined effect of PPGC+S and BDNF on the survival of mesenchymal stem cells (MSCs) from osteoporotic and non-osteoporotic female donors.MethodsIn our study, cells were seeded on PPGC+S plates with the following mineral composition of C+S of (a) 5:5, (b) 3:7, and (c) 0:10 (PPGS 0:10). Apoptosis and necrosis were measured after the addition of BDNF, followed by light microscopic analysis.ResultsThe application of BDNF resulted in reduced necrosis and apoptosis in all biomaterials. The lowest level of necrosis was found in the PPGC+S 5:5 group. Apoptosis was most reduced in the PPGC+S 3:7 group, although the difference compared to PPGC+S 5:5 was not statistically significant. No differences were observed between MSCs from osteoporotic and non-osteoporotic donors.ConclusionThus, PPGC+S 5:5 appears to be the most suitable composition for bone healing, especially when supplemented with BDNF.